2009
DOI: 10.1093/abbs/gmp045
|View full text |Cite
|
Sign up to set email alerts
|

Study on docetaxel-loaded nanoparticles with high antitumor efficacy against malignant melanoma

Abstract: Docetaxel (Doc) has extraordinary activities against a variety of solid tumors. However, the clinical efficacy of Doc is limited due to its poor solubility, low selective distribution, fast elimination in vivo, etc. In the present study, Doc was incorporated into the core-shell structure of nanoparticles prepared based on our previous work. The obtained docetaxel-loaded nanoparticles (DOCNP) were characterized with various biophysical methodologies, and its antitumor efficacy against malignant melanoma was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…In order to improve the aqueous solubility of DTX, the commercial preparation Taxotere contains a high concentration of the nonionic surfactant Tween 80 (polysorbate 80), 5 which unfortunately leads to serious side effects, such as hypersensitivity, nephrotoxicity, neurotoxicity, and incompatibility with common polyvinyl chloride intravenous administration sets. 6 In previous reports, various drug delivery systems have been developed to replace the Tween 80-based vehicle for overcoming the aforementioned limitation, including an HP-β-cyclodextrin inclusion complex, 7 nanoparticles, 8 liposomes, 9 and microemulsions. 10 Among these delivery systems being applied to DTX, polymeric micelles are considered one of the strongest potential alternatives since several micellar formulations have been under clinical evaluation as carriers for anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the aqueous solubility of DTX, the commercial preparation Taxotere contains a high concentration of the nonionic surfactant Tween 80 (polysorbate 80), 5 which unfortunately leads to serious side effects, such as hypersensitivity, nephrotoxicity, neurotoxicity, and incompatibility with common polyvinyl chloride intravenous administration sets. 6 In previous reports, various drug delivery systems have been developed to replace the Tween 80-based vehicle for overcoming the aforementioned limitation, including an HP-β-cyclodextrin inclusion complex, 7 nanoparticles, 8 liposomes, 9 and microemulsions. 10 Among these delivery systems being applied to DTX, polymeric micelles are considered one of the strongest potential alternatives since several micellar formulations have been under clinical evaluation as carriers for anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, we evaluated the anticancer efficiency of drug loaded nanoparticles by intratumoral delivery in our previous reports. Cisplatin and Doc was used as model drugs incorporated into nanoparticles formed by amphilic copolymers, demonstrating exciting in vivo anticancer efficacy (14,22). Compared with free drugs, nanoparticle-based drug delivery systems are characterized by the controlled release of incorporated drugs, which may overcome the deficiency of necessary drug retention in the tumor and may reach a satisfying outcome in improving antitumor efficacy when combined with intratumoral delivery instead of intravenous route.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of body weight variations could be partially used to define the adverse effects of the different therapy regiments. 37 Therefore, pLNS and tLNS generated less toxicity to mice than Duopafei when administered intravenously under the present experiment condition, which will facilitate its future clinical application. Moreover, it was observed that the mice of the Duopafei group were in a weak state and moved slowly; three of these mice died during the experiment, whereas no obvious alteration was observed in the pLNS and tLNS group.…”
Section: Dtx Concentration (µM) Cell Viability (%)mentioning
confidence: 73%